2002
DOI: 10.1046/j.1432-1033.2002.02973.x
|View full text |Cite
|
Sign up to set email alerts
|

EPR characterization of the mononuclear Cu‐containing Aspergillus japonicus quercetin 2,3‐dioxygenase reveals dramatic changes upon anaerobic binding of substrates

Abstract: Quercetin 2,3‐dioxygenase (2,3QD) is a copper‐containing dioxygenase that catalyses the oxidation of the flavonol quercetin to 2‐protocatechuoylphloroglucinol carboxylic acid with concomitant production of carbon monoxide. In contrast to iron dioxygenases, very little is known about copper dioxygenases. We have characterized 2,3QD from the fungus Aspergillus japonicus by electron paramagnetic resonance spectroscopy (EPR). At pH 6.0, 2,3QD shows a mixture of two EPR species. The major form has parameters typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
86
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 29 publications
6
86
0
1
Order By: Relevance
“…Endoperoxide intermediate 4 represents the most convenient structure to rationalize first the release of carbon monoxide and then the formation of the depside-bound form 5 of the enzyme, for which a putative signal corresponding to a trigonal bipyramidal geometry has been observed by EPR spectroscopy (10). Carbon monoxide liberation would occur with the breakage of one OOO and two COC bonds.…”
Section: Formation Of the E⅐s Complex And Role Of Glumentioning
confidence: 99%
See 2 more Smart Citations
“…Endoperoxide intermediate 4 represents the most convenient structure to rationalize first the release of carbon monoxide and then the formation of the depside-bound form 5 of the enzyme, for which a putative signal corresponding to a trigonal bipyramidal geometry has been observed by EPR spectroscopy (10). Carbon monoxide liberation would occur with the breakage of one OOO and two COC bonds.…”
Section: Formation Of the E⅐s Complex And Role Of Glumentioning
confidence: 99%
“…Quercetin 2,3-dioxygenase (2,3QD) belongs to the cupin superfamily (6,7) and is the only dioxygenase unambiguously known to rely on a mononuclear copper center for activity (8)(9)(10). It is a type 2 copper-dependent enzyme expressed by Aspergillus species when grown on complex aromatic compounds, such as rutin or quercetin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is also reinforced by the fact that QdoI is an intracellular enzyme, 24) and thus different from the secreted type of Aspergillus enzymes. 7,8,10) Correlation between QdoI activity and quercetin susceptibility…”
Section: Susceptibility To Flavonoidsmentioning
confidence: 99%
“…The gene encoding quercetin 2,3-dioxygenase has been cloned from A. japonicus, Streptomyces sp., and B. subtilis. 5,9,10) The crystal structures of the enzymes from A. japonicus and B. subtilis revealed that both enzymes belong to the bicupin family, which accommodates metal ions in their catalytic active sites, formed by characteristic -barrel domains. 8,11) While the fungal enzyme contains Cu 2þ , 8,12) the enzyme from B. subtilis is assumed to prefer Mn 2þ as a cofactor, 13) but its recombinant protein has been purified as an iron enzyme from Escherichia coli.…”
mentioning
confidence: 99%